Pengelolaan Sumber Daya Alam Danau Batu Menuju Keseimbangan Ekosistem - Yanti, Elyta Vivi (Jurnal sosial dan sains, 2025)
A lake is a large basin on the earth's surface that is inundated by fresh or saltwater that is surrounded by land, and is the source of human life. Batu Lake is located in Sigi Village, Central Kahayan District, Pulang Pisau Regency, Central Kalimamtan Province. The area of this lake is approximately 12 km2, around there are rafts and residential areas, the distance from the capital of Central Kahayan District (Bukit Rawi + 3 km) is located a little in. Batu Lake is a waterway that is the lifeblood of the livelihood of the people around Sigi Village. The community has knowledge about Lake Batu that has existed since the Dutch era until now this knowledge guides the community on how to behave positively and the form of responsibility given around Lake Batu so that with knowledge supported by local culture, Lake Batu can be maintained. A form of positive behavior of the community in preserving Batu Lake is that the community does not use fish poison in catching fish, does not throw garbage around Batu Lake, does not say dirty and takabur around Batu Lake.